Effect of Storage of Records on Employee Performance at The National Land Commission in Nairobi, Kenya. - Chepkoech, Langat Rose; Omare, Mongare; Kamau, Geoffrey (The International Journal of Business Management and Technology, 2023)
The Ministry of Lands still heavily relies on manual record-keeping systems, which adversely impact employee performance and record management. The absence of modern technological infrastructure, such as electronic document management systems, hinders efficient record storage, retrieval, and maintenance. The study sought to assess the effect of storage of records on employee performance at the national land commission in Nairobi, Kenya. The study was anchored on the restricted access and limited control. The study adopted a descriptive research design. The unit of analysis was 10 directorates at the National Land Commission in Nairobi. The unit of observation was 439 staff at the National Land Commission in Nairobi. Nassiuma’s 2008 formula was adopted to determine a sample of 115 respondents. The study further used stratified random sampling to select a sample of employee from each of the 10 directorate. The study used questionnaires as the instrument of data collection. The study used content and face validity. An internal consistency technique was adopted by utilization of Cronbach’s Alpha to measure the reliability of the instruments. Data was analyzed using SPPS version 25. The study used descriptive and inferential statistics. The findings of the study was presented using frequency tables. The study findings revealed that the organization has guidelines to store records both sensitive and classified records which save time hence higher employee productivity. The study concluded that there exists a strong positive and significant relationship (r = .741, P=0.027) between storage of records and employee performance at the national land commission in Nairobi, Kenya. From the findings the study recommended that the Ministry of Lands should also ensure that the ERMS is user-friendly and accessible to all stakeholders, establish a helpdesk or customer service center, integrate the ERMS with other relevant government systems, establish a mobile application for the ERMS, and ensure that the ERMS is accessible to persons with disabilities.
Keywords: Storage of Records; Employee Performance; National Land Commission